Ubiquitin-proteasome pathway in skeletal muscle atrophy - Pang, XiangSheng; Zhang, Peng; Chen, XiaoPing; Liu, WenMing (Frontiers in Physiology, 2023)
Skeletal muscles underpin myriad human activities, maintaining an intricate balance between protein synthesis and degradation crucial to muscle mass preservation. Historically, disruptions in this balance-where degradation overshadows synthesis-have marked the onset of muscle atrophy, a condition diminishing life quality and, in grave instances, imperiling life itself. While multiple protein degradation pathways exist-including the autophagy-lysosome, calcium-dependent calpain, and cysteine aspartate protease systems-the ubiquitin-proteasome pathway emerges as an especially cardinal avenue for intracellular protein degradation, wielding pronounced influence over the muscle atrophy trajectory. This paper ventures a panoramic view of predominant muscle atrophy types, accentuating the ubiquitin-proteasome pathway's role therein. Furthermore, by drawing from recent scholarly advancements, we draw associations between the ubiquitin-proteasome pathway and specific pathological conditions linked to muscle atrophy. Our exploration seeks to shed light on the ubiquitin-proteasome pathway's significance in skeletal muscle dynamics, aiming to pave the way for innovative therapeutic strategies against muscle atrophy and affiliated muscle disorders.